A molecular dynamics simulation study to investigate the effect of C60 on thermo- mechanical and elastic properties of DGEBA/DETA nanocomposites - TALUKDAR, Dhritiman; HALDER, Sudipta; DAS, Subhankar; GOYAT, M.S.; MISHRA, Abhishek Kumar (Journal of Metals, Materials and Minerals, 2022)
Molecular dynamics simulations were performed to investigate the effect of fullerenes (C60) on the thermal and mechanical properties of a cross-linked epoxy system composed of epoxy resin DGEBA and curing agent DETA. Hence, a comparative investigation was performed on the thermal and mechanical properties of DGEBA/DETA reinforced with 2.3 wt% C60 and neat epoxy systems. Properties such as glass transition temperature (GTT), coefficients of thermal expansion (CTE), and elastic properties at different cross-linking densities. Simulation results indicated that the GTT of the epoxy increased by about 25 K due to the presence of C60. The effect of C60 on the CTE was very less, and at higher crosslinking densities, an increase in CTE before the glass transition was observed. It was also observed that the effect of C60 on mechanical properties is dependent on the crosslinking density. The young’s modulus of the epoxy/C60 system at a high strain rate showed a drastic decrease as compared to the neat epoxy system at higher crosslinking densities. The highest value of young’s modulus of the epoxy/C60 system was observed at 65% crosslinking density.